THE EFFECTIVENESS OF ETHNOMATEMATICS BASED LEARNING ON MATHEMATICS ABILITY OF ELEMENTARY SCHOOL STUDENTS: A META-ANALYIS STUDY - Sulistyowati, Endang; Mawardi, Dona Ningrum (UIN Sunan Kalijaga Yogyakarta, 2023)
The combination of culture and mathematics can provide more meaningful mathematics learning so that the abstraction of mathematical material can be more easily understood by students. However, previous research investigating the effectiveness of implementing ethnomathematics-based learning in elementary schools has shown mixed results. Therefore, the purpose of this study was to determine the effectiveness of ethnomathematics-based learning on the mathematical abilities of elementary school students. The method used in this study is meta-analysis. This study analyzed 13 effect sizes from 12 primary studies that met the inclusion criteria. The results of the study based on the moderator variable showed that the effectiveness of applying ethnomathematics-based learning to elementary students' mathematical abilities differed significantly based on the year of publication (Qb = 10.22; p = 0.00), but there was no significant difference based on the class level variable (Qb = 1.98; p = 0.16) and the sample size variable (Qb = 0.30; p = 0.58). These findings provide evidence that ethnomathematics-based learning can be effective in improving elementary school students' mathematical abilities. However, the varying results between studies could be due to other factors to consider. The results of this study can be a basis for policy makers and education practitioners to choose the right learning approach in improving the quality of learning mathematics in elementary schools. Further understanding of the factors that influence the effectiveness of ethnomathematics-based learning is also important for the development of a more optimal approach in this context.